2011
DOI: 10.1007/s00262-011-1041-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunoediting and persistence of antigen-specific immunity in patients who have previously been vaccinated with NY-ESO-1 protein formulated in ISCOMATRIX™

Abstract: Immunoediting suggests that a signal of anti-tumour activity was observed in high-risk resected melanoma patients vaccinated with NY-ESO-1/ISCOMATRIX™. This was associated with measurable persisting immunity in the majority of vaccinated subjects tested. A prospective randomised trial has been undertaken to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…5 Importantly, our results confirm and extend the results of previously published papers 4,8,24,25 by demonstrating the presence of immunodominant regions of NY-ESO-1 proteins (NY-ESO-1 79-108 and NY-ESO-1 115-138 ), which showed a high level of immunogenicity in a large proportion of vaccinated patients. Of note, it has previously been shown that vaccination strategies based on the injection of recombinant NY-ESO-1 protein in Montanide and CpG resulted in the expansion of NY-ESO-1 specific CD8…”
supporting
confidence: 81%
See 1 more Smart Citation
“…5 Importantly, our results confirm and extend the results of previously published papers 4,8,24,25 by demonstrating the presence of immunodominant regions of NY-ESO-1 proteins (NY-ESO-1 79-108 and NY-ESO-1 115-138 ), which showed a high level of immunogenicity in a large proportion of vaccinated patients. Of note, it has previously been shown that vaccination strategies based on the injection of recombinant NY-ESO-1 protein in Montanide and CpG resulted in the expansion of NY-ESO-1 specific CD8…”
supporting
confidence: 81%
“…We compared the profile of cytokine production by NY-ESO-1 specific T cells at baseline (i.e., pre-vaccination samples), during the ISCOMA-TRIX priming stage (include Week 5, 9,13) and during the rF-NY-ESO-1 boosting stage (include Week 17,21,25). Supporting Information Figure S4 shows the data from 18 Arm A and 21 Arm B patients stimulated with the NY-ESO-1 peptide pool spanning the full length NY-ESO-1 protein.…”
Section: Poly-functional Cd4mentioning
confidence: 99%
“…Similarly, T-cell responses were detected in the majority of individuals receiving an HCVcore/ISCOMATRIX vaccine (Drane et al, 2009). Furthermore, similar broad epitope immune responses were generated in cancer patients expressing NY-ESO-1 + tumours and these were sustained for several years (Davis et al, 2004;Ebert et al, 2009;Nicholaou et al, 2011).…”
Section: Iscomatrix Adjuvant Consistently Stimulates Robust and Readimentioning
confidence: 74%
“…This results in both robust and effective Ab and CD8 + T-cell responses. Generation of highfrequency antigen-specific CD8 + T-cell responses is a reproducible feature of ISCOMATRIX vaccines in animals and humans (Davis et al, 2004;Ebert et al, 2009;Drane et al, 2009;Nicholaou et al, 2011), as this is not readily (or weakly at best) detected with other adjuvant systems.…”
Section: Iscomatrix Adjuvant In Prophylactic Vaccinesmentioning
confidence: 99%
“…However, persisting immune responses are also capable of altering the phenotype of the tumor via a process known as immunoediting or immunosculpting. For example, in patients with melanoma treated with NY-ESO-1 vaccine and immune adjuvant, histologic analysis of tumor samples from patients who relapsed following treatment showed a loss of NY-ESO-1 antigen and human leukocyte antigen expression necessary for immune activation (10,11). This suggests immunoediting selects for tumor variants with little or no immunogenicity and may result in tumor responses to immunotherapies decreasing or reversing over time.…”
Section: Introductionmentioning
confidence: 99%